Economic liberalisation targeted programmes and household food security: a case study of India - Dev, S. Mahendra; Ravi, C.; Viswanathan, Brinda (International Food Policy Research Institute, 2004)
Although there is little consensus on the impact of trade liberalization on poverty and food security, it is nevertheless widely acknowledged that there is a need for governments to establish safety-nets to guard against any potentially harmful effects on the poor and vulnerable sections of society. Against this background, programs aimed at achieving food security and reducing poverty gain increased importance in the reform era. This study aims to evaluate several such programs that are currently in place in the country from the point of view of their impact, efficiency and financial sustainability. The purpose is to determine how these programs may be improved and propose appropriate policy options for reform, while also keeping in mind the new challenges that might lie ahead. Specifically, the study evaluates the Public Distribution System (PDS), Public Works Programs, and certain food-based direct intervention programs such as the Integrated Child Development Scheme (ICDS) and Tamil Nadu Integrated Nutrition Program (TINP), with a view to suggest how they can be made more cost effectiveness and better targeted. -- From Author's Executive Summary